2014
DOI: 10.1089/lap.2013.0459
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cosmetic Outcomes After Robotic/Endoscopic Thyroidectomy by a Gasless Unilateral Axillo-breast or Axillary Approach

Abstract: Long-term postoperative cosmesis after robotic/endoscopic thyroidectomy using GUAB/GUA approaches is significantly better than conventional open thyroidectomy. In the robotic/endoscopic group, the scarless breasts resulting from the GUA approach lead to greater satisfaction than those after the GUAB approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 19 publications
0
52
0
2
Order By: Relevance
“…Robotic thyroidectomy using a GUA or GUAB approach has advantages, the most significant of which is the excellent cosmetic outcome without scars on the anterior neck [18]. Identification of the RLN and parathyroid glands is subjectively easier than in conventional thyroidectomy, and delicate dissection of the thyroid gland is possible with the 3-dimensional magnified view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robotic thyroidectomy using a GUA or GUAB approach has advantages, the most significant of which is the excellent cosmetic outcome without scars on the anterior neck [18]. Identification of the RLN and parathyroid glands is subjectively easier than in conventional thyroidectomy, and delicate dissection of the thyroid gland is possible with the 3-dimensional magnified view.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, with regard to the postoperative cosmetic satisfaction and functional outcomes, we previously reported that swallowing function, neck discomfort and paresthesia, and overall quality of life (QOL) after robotic thyroidectomy were similar to those after conventional cervical thyroidectomy and that postoperative cosmesis and voice outcomes were better in the robotic group [15][16][17][18][19][20]. Also, we and other authors demonstrated that the surgical completeness of robotic total thyroidectomy by transaxillary approach was comparable to that of conventional thyroidectomy if the procedure was performed in properly selected patients by expert robotic thyroid surgeons [21][22][23].…”
mentioning
confidence: 99%
“…Vascularity, pigmentation, and height of the scar are scored from 0 to 3, and pliability is scored from 0 to 5. The score is the sum of four domains, with a score of 0 representing normal skin and a score of 14 representing the worst scar [11]. …”
Section: Methodsmentioning
confidence: 99%
“…(2) How satisfied are you with the contour of the neck? Each question was scored as 0 (very satisfied), 1 (satisfied), 2 (average), 3 (dissatisfied), and 4 (very dissatisfied) [11]. Scar consciousness was assessed with four questions: (1) Do you think others look at your neck scar?…”
Section: Methodsmentioning
confidence: 99%
“…As for the length of hospital stay, while conflicting results were reported by earlier data [1][2][3], a recent metaanalysis revealed no significant difference between robotic-assisted thyroidectomy and open thyroidectomy [6 && ]. Cosmetic satisfaction was evaluated in six studies at different postoperative time-points [15,16,23,28,29,38] and was consistently found to be higher in robotic-assisted thyroidectomy than in open thyroidectomy. Except for two studies reporting significantly less pain in robotic-assisted thyroidectomy on the first 2 postoperative days [26,28], no difference was observed between robotic-assisted thyroidectomy and open thyroidectomy for postoperative pain scores [15,16,24,29] and analgesic requirement [15,24,26] in four other studies.…”
Section: Robotic Thyroidectomymentioning
confidence: 99%